Numerical Study of Atmospheric Icing on Non Rotating Circular Cylinders in Tandem Arrangement - Virk, Muhammad Shakeel (The Journal of Computational Multiphase Flows, 2013)
Link to publishers version: http://journals.sagepub.com/doi/pdf/10.1260/1757-482X.5.1.73 Creative Commons Attribution License or Creative Commons Attribution Non-Commercial License Numerical study of atmospheric ice accretion on two non-rotating circular cylinders in tandem arrangement was carried out at different operating and geometric conditions. To validate the numerical model, initially the results of ice accretion on single circular cylinder were compared with the experimental data obtained from CIGELE atmospheric icing research wind tunnel (CAIRWT) [1, 2]. A good agreement was found between experimental and numerical results. Numerical analyses of ice accretion on two circular cylinders in tandem arrangement showed that accreted ice loads decreases with the increase in distance between the cylinders and also affects the rate and shape of ice accretion. Parametric study at different droplet sizes and temperatures showed a significant change in ice accretion. This research work provides a useful base for better understanding and further investigation of atmospheric ice accretion on circular overhead power network cables in tandem arrangement, installed in the cold regions.